2012
DOI: 10.1353/hpu.2012.0178
|View full text |Cite
|
Sign up to set email alerts
|

Individual Breast Cancer Risk Assessment in Underserved Populations: Integrating Empirical Bioethics and Health Disparities Research

Abstract: Research suggests that individual breast cancer risk assessment may improve adherence to recommended screening and prevention guidelines, thereby decreasing morbidity and mortality. Further research on the use of risk assessment models in underserved minority populations is critical to informing national public health efforts to eliminate breast cancer disparities. However, implementing individual breast cancer risk assessment in underserved patient populations raises particular ethical issues that require fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…13,14 Yet, we know that minority and underserved populations are less often aware of their breast cancer risk 38,39 and breast density, 21,40,41 and fewer receive breast cancer risk assessment. 42 This suggests that equitable care downstream of learning one's breast density has not yet been achieved. Achieving timely access to these services for non-English speakers is an important step in promoting equity in evidence-based breast cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Yet, we know that minority and underserved populations are less often aware of their breast cancer risk 38,39 and breast density, 21,40,41 and fewer receive breast cancer risk assessment. 42 This suggests that equitable care downstream of learning one's breast density has not yet been achieved. Achieving timely access to these services for non-English speakers is an important step in promoting equity in evidence-based breast cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…These authors highlighted the fact that complexities inherent to personalized risk assessment could disadvantage people from certain ethnic and socioeconomic groups due to a lower uptake (Chowdhury et al 2013). Anderson & Hoskins maintained that more research "on the use of risk assessment models in underserved minority populations is critical to informing national public health efforts to eliminate breast cancer disparities" (Anderson and Hoskins 2012). They supported their claim by the knowledge gap of how the relationships between breast cancer and genetics can affect underserved minority women.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the literature has reported that: risk perception is affected by health literacy, health numeracy, and cultural beliefs (Anderson and Hoskins 2012); limited health literacy poses a particular challenge to communicating with underserved communities about genomics (Lea et al 2011); people with lower health literacy may not be able to take advantage of precision medicine in the same ways as those with higher health literacy (Ferryman and Mikaela 2018); risk is a difficult concept that is not well understood by the public (Lea et al 2011); and even a well-educated population might not fully understand the terminology associated with genetic testing (Hooker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations